Clinical predictors and radiological reliability in atlantoaxial subluxation in Down's syndrome. Issue 7 (July 1991) - Selby, K A; Newton, R W; Gupta, S; Hunt, L
Abstract : Clinical signs and symptoms that might predict atlantoaxial subluxation were studied prospectively in 135 of 180 children with Down's syndrome aged 6-14 years who form the Hester Adrian Research Centre cohort. Lateral radiographs of the cervical spine were taken in flexed, extended, and neutral positions, and the percentage of abnormalities in each view was 14, 10, and 10%, respectively. Gait was the only significant clinical predictor. The relative risk of having an abnormal neck radiograph with an abnormal gait was 2.91 (95% confidence interval (CI) 1 to 8). The sensitivity was 50% and the specificity 81%. Nineteen children had repeat radiographs to assess the reliability of radiological diagnosis. Six had abnormalities; five of 19 (26%) had an abnormality on the first radiograph, and four of 19 (21%) had an abnormality on a second radiograph, but only three (15%) had an abnormality on both occasions in any view (95% CI 0 to 25). We conclude that radiographs of the cervical spine are unreliable at identifying atlantoaxial subluxation in children with Down's syndrome, and we failed to identify any reliable clinical predictor.